THE HEAMODYNAMIC RESPONSE TO THE CRUDE AQUEOUS EXTRACT OF CRINUM MACOWANII BULBS (CAEB) IN ANAESTHETIZED WISTAR RATS - Burger, A.; Persson, K.; Mugabo, P.; Green, I. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Crinum macowanii is used in traditional medicine. To increase efficacy and safety we evaluated the haemodynamic effect of the CAEB. CAEB was administered via the jugular vein after sodium pentobarbitone anaesthesia (40 mg/kg, i.p.) and tracheostomy. The rats were placed on a heating pad at 37ºC. A Powerlab© using Deltran II© pressure transducers monitored femoral arterial pressure (BP). The heart rate (HR) was determined from BP. The data is reported as mean±SD (n=6) with significance set at P<0,05. Psys increased significantly from 125±3 mmHg at baseline to 180±19 mmHg at 0,2 mg/kg. After this dose there was a significant decrease in Psys with increased [CAEB] to 60±4 mmHg at 0,3 mg/kg. Pdiast peaked at 0,2 mg/kg (123±14 mmHg). This was not significantly relative to baseline (95±9 mmHg, n = 6). Pdiast did however decrease significantly (compared to the peak value at 0,2 mg/kg) at 0,25 mg/kg (90±13 mmHg) and 0,3 mg/kg (34±3 mmHg). The pulse pressure showed a non-significant tendency to increase up to 0,2 mg/kg followed by decreases at 0,25 and 0,3 mg/kg but due to large SDs this was not significant at any of the applied dosages. HR had a relatively flat response over the dose range but was significantly increased relative to the baseline at all doses with the exception of 0,05 mg/kg. CAEB thus had a tachycardic effect at all doses with increased Psys up to and including 0,2 mg/kg, but it decreased Psys and Pdiast at doses higher than 2 mg/kg (0,25 mg/kg and 0.3 mg/kg).